S24 CT characteristics in culture-proven NTM infection in non-CF bronchiectasis: a poor diagnostic tool?. (December 2018) - Easton, F; Elsayed, M; Malin, A
Abstract : Background: Non-tuberculous mycobacterial pulmonary disease (NTM PD) presents a difficult clinical challenge. The presentation varies from transient respiratory pathogen to aggressive destruction, relying heavily on clinical symptoms, effective sputum culture and imaging. Although CT is a reliable and non-invasive method for diagnosing non-CF bronchiectasis, features of NTM PD on CT imaging are nonspecific and often undistinguishable from underlying respiratory conditions, concurrent infection or inflammation. NTM prevalence is increasing worldwide and non- CF bronchiectasis remains an important risk factor. Despite improved BTS/ATS guidance for treatment, the lack of specific CT findings in non-CF bronchiectasis patients makes decision to treat problematic. Patients and methods: A retrospective analysis of CT reports of 261 consecutive non-CF bronchiectasis patients at Royal United Hospital, Bath was undertaken. Reports were scrutinised for the presence of seven CT characteristics: tree in bud, pulmonary nodules or nodularity, consolidation, cavitation, ground glass change, pleural thickening and pleural effusion. NTM culture status was recorded for each patient but Mycobacterium gordonae cases were classified as non-NTM. CT findings were compared between NTM positive sputum culture cases and NTM negative cases using Chi-squared for statistical significance between groups (SPSS version 24). Results: 261 patients with non-CF bronchiectasis were identified. Of these 27 (10.3%) had positive NTM sputum culture (MAC 16 (59.3%), M. abscessus 5 (18.5%), M. chelonae 4 (14.8%), M. malmoense 1 (3.7%), M. xenopi 1 (3.7%)). In total the incidence of specific CT findings was as follows; tree and bud 50 (19.2%), nodules/nodularity 97 (37.2%), consolidation 51 (19.5%), cavitation 8 (3.1%), ground glass 30 (11.5%), pleural thickening 13 (5.0%), pleural effusion 10 (3.8%). 103 patients (39.5%) had none of these characteristics reported. There was no statistically significant difference in the presence or absence of CT signs in patients with NTM and no NTM (see table 1). Conclusions: In non-CF bronchiectasis there appears to be no reliable CT findings to identify patients with NTM infection. There a remains a need for a high level of clinical suspicion in patients with bronchiectasis and microbiology remains the mainstay of diagnosis.